Eidetics of Law-Making Acts: Parts, Wholes and Degrees of Existence - Francesca De Vecchi (Rosenberg & Sellier, 2017)
In my paper I introduce the phenomenological concept of “eidetics” and its application to law. I show that, according to this approach grounded in the works of Reinach (1913/1989) and Stein (1925), the problem of the existence and validity of the law can be fruitfully analysed in terms of parts-wholes which constitute law-making acts as wholes, both as performed and fulfilled acts. I argue that the parts of law-making acts can be subject to varying degrees of constraint – necessary, possible or contingent parts – and that it is the possible part of law-making acts that makes the difference between the existence of law-making acts and their validity: between their mere existence as performed acts, and their full existence as fulfilled and valid acts. I show this in focusing on Stein’s suggestion of filling the inter-personal gap between legislator and citizens in legal provisions by introducing “integrative acts”, which facilitate the uptake and, consequently, the enforcement of legal provisions by citizens. I suggest that Stein’s work on the integrative acts of legal provisions is grounded in the eidetic claim that essential parts of a whole also include possible – and not only necessary – parts, and that these are essential relations of tendency: legal provisions tend essentially to be fulfilled and their existence acquires a full sense only when they are enforced. Finally, I deal with eidetics and the issue of degrees and quality of existence in social ontology.